Affection and disciplinary style perceived by children in residential care: relationships with quality standards in residential care. - Gaitán, Sabina D.; Fernández Sánchez, Joanna; Salas-Martínez, María Dolores; García-Martín, Miguel Ángel; Palma-García, María de las Olas (My University, 2024)
Residential foster care is still an essential resource to protect children. In Spain there are 16,000 children in residential care, therefore it is necessary to continue improving quality in residential childcare. This study analyzed how foster children and youth perceive the quality of care in the residential home, the affective relationships (affection/communication and criticism/rejection) and the discipline style of caregivers. Also studied was the relationship between quality of the residential home and with affection and disciplinary style. Forty-six boys and girls aged between 10 and 16 years old, from seven residential centers in Malaga (Spain), participated in the study. An ad hoc questionnaire based on the Quality Standards (EQUAR) was created to evaluate quality of care in the residential home. Warmth Scale (EA) and the Rules-Demands Scale (ENE) were used to asses affection and discipline style of caregivers. The results showed that: 1) foster children evaluate the quality of care positively, 2) they perceive more affection/communication than criticism/rejection by the caregivers and, mostly, inductive and authoritarian discipline, 3) when they perceive more affection/communication (and less criticism/rejection) and more inductive styles, they also evaluate with higher scores the quality of the foster home. These results show that children and youth perceive the quality of care provided in residential care programs positively, and perceive higher quality care, when they perceive more affection, less rejection, and more appropriate discipline styles. Future studies could provide information on whether the quality of care influences the affective relationships and the discipline styles displayed by caregivers.
Keywords: Niños institucionalizados; Afecto (Psicología); Disciplina; Affection style; Disciplinary style; Residential care; Quality standards